Gambaran Gaya Hidup dan Kejadian Penyakit Diabetes Melitus Tipe II di Desa Paranglompoa Kecamatan Bontolempangan Kabupaten Gowa - Samudra Samudra; Muhamad Isnaini; Rudi Salam; Asrul Muarif (Fatiakara Care: Jurnal Ilmiah Keperawatan, 2026)
An unhealthy lifestyle, combined with an irregular eating pattern, triggers a decline in health levels and increases the risk of various diseases, including Diabetes Mellitus. Diabetes mellitus is a chronic condition that occurs when the body cannot produce enough insulin or cannot use insulin effectively. The purpose is to determine the lifestyle and incidence of Type II diabetes mellitus in Paranglompoa village, Bontolempangan sub-district, Gowa district. The type of research used is quantitative with a descriptive design. The results of the research conducted in Paranglompoa Village show that the majority of respondents have a fairly good lifestyle, with 30 people (71%). Meanwhile, only 5 respondents (12%) have a good lifestyle, and the remaining 7 people (17%) have a less than ideal lifestyle. Based on the research involving 42 respondents regarding lifestyle and the occurrence of Type II Diabetes Mellitus, it can be concluded that the majority of respondents have a lifestyle in the fair category. Although not considered poor, a fair lifestyle is still not ideal and has the potential to increase the risk of diabetes if it is not immediately improved to a consistent healthy lifestyle.